#RadialFirst and #RadialForNeuro: A descriptive analysis of Twitter conversations regarding transradial access. Issue 5 (October 2021) - Robertson, Faith C; Linzey, Joseph R; Alotaibi, Naif M; Regenhardt, Robert W; Harker, Pablo; Vranic, Justin; Dmytriw, Adam A; Koch, Matthew J.; Stapleton, Christopher J; Leslie-Mazwi, Thabele M; Patel, Aman B
Background: Transradial access for neurointerventional procedures was adopted and modified from cardiovascular intervention and is increasingly established as a safe and effective alternative to transfemoral catheterization. As social media influences public opinion on medical treatment, this study analyzes Twitter conversations to elucidate social media's depiction of transradial access as a neurointerventional tool. Materials and methods: Twitter hashtags #RadialFirst and #RadialForNeuro were evaluated using a mixed-method analysis of quantitative social media metrics and qualitative thematic analysis. Results: Between January 2015 and April 2020, 104, 146 tweets from 141 countries employed the hashtag #RadialFirst (2015 (1); 2016 (0); 2017 (22, 804); 2018 (33, 074); 2019 (38, 352); 2020 (9, 915 January-April)). These generated 226, 909, 374 impressions and were retweeted 80, 120 times by 13, 707 users. Media was present in 62.5% of tweets (e.g. wrist image, angiographic runs) but only 14.5% had a reference article. Physicians authored 70.8% of tweets; interventional cardiologists accounted for 83% of top 100 influencers. #RadialForNeuro is more nascent (6 posts in 2019; 323 posts January–April 2020), with 392, 662 impressions, and 254 retweets by 177 users; physicians authored 35.6%. Compared to #RadialFirst, #RadialforNeuro tweets were more likely to include media (76%), less likely to include citations (9.7%), and more likely to discuss complications and troubleshooting techniques. Conclusion: Twitter activity regarding transradial access permits information dissemination and discussion on approach benefits and challenges. However, many posts arise from non-physician sources and lack links to peer-reviewed publication. The public should be mindful that tweets may reflect opinions, rather than experience or scientific evidence.